Pre- and post-irradiation performance of FBK 3D silicon pixel detectors for CMS - Krzywda, A; Alagoz, E; Bubna, M; Obertino, M; Solano, A; Arndt, K; Uplegger, L; Betta, G; Boscardin, M; Ngadiuba, J; Rivera, R; Menasce, D; et al. (Elsevier, 2014)
In preparation for the tenfold luminosity upgrade of the Large Hadron Collider (the HL-LHC) around 2020, three-dimensional (3D) silicon pixel sensors are being developed as a radiation-hard candidate to replace the planar ones currently being used in the CMS pixel detector. This study examines an early batch of FBK sensors (named ATLAS08) of three 3D pixel geometries: 1E, 2E, and 4E, which respectively contain one, two, and four readout electrodes for each pixel, passing completely through the bulk. We present electrical characteristics and beam test performance results for each detector before and after irradiation. The maximum fluence applied is 3.5×1015 n eq/cm2. © 2014 Elsevier B.V.